Sempurna Enterprise : Wemo Light Switch / Ahmad Fahmi Kamalul Arifin ...[et al.] - Kamalul Arifin, Ahmad Fahmi; Mohd Ikbal, Mohamad Shafirul Nazmi; Azman, Muhammad Haziq; Hashim, Muhamad Haziq; Mohd Izzat Asyraf Teh, Haziq Hilmi (2017)
Sempurna Enterprise is a company which focuses on servicing of WeMo light switch in Malaysia. WeMo light switch is the most popular light switch in USA. This product become popular because it does not require to much energy from people which they can only turn on the light of their house by using their smartphones. Based on the objectives above, we are venturing into services industry. WeMo production has the potential of being a profitable business if it is done in modern way with large scale and systematically managed. We will expect that our business will become more developed in the near future because with the new innovation in our services, the demand will increase not only durrng any occasion but it might be a new daily snack. This will give more advantages for us to make our product more profitable and stable in the long run.